Evolving Hangwuran City Development Model Through Partial Least Square Approach in North-Central Nigeria - Medayese, Samuel; Magidimisha-Chipungu, Hangwelani H; Chipungu, Lovemore (UI Scholars Hub, 2024)
The need for a paradigmatic shift in city development ideology has become increasingly evident over the years. In response to this need, the Hangwurian City Development Model was developed to establish a connection between the concepts of environmental awareness, urban governance, and management. This model also integrates sustainable urban development, urban liveability, and inclusive physical development. The research sets a critical objective of analyzing the significant levels of various indicator variables. The exploratory research utilized partial least squares (PLS) via SmartPLS to evaluate the variables, collecting quantitative data through the open data toolkit from three selected cities: Lokoja, Minna, and Lafia in North-Central Nigeria. The study sampled 843 respondents across the cities, randomly selected among residents aged 18 years and older, with a focus on household heads as the unit of measurement. The research findings indicate that most of the examined variables have Cronbach's Alpha above 0.7, and most of the retained variables have a significance value greater than or equal to 0.7. The average variance explained by the indicators was very substantial, with most falling within the 0.5 to 0.6 range. Therefore, the research recommends that, due to the significance of the indicators and the validity of the internal and external data, this model can be applied as a procedural framework to guide city development on a regional scale. Consequently, it was concluded that for city development to progress and evolve without the issues that Hangwurian city development aims to address, it must be approached through the interconnectedness and significance of environment, governance, sustainability, liveability, and inclusion.